Extranodal Extension Is an Independent Prognostic Factor in Papillary Thyroid Cancer: A Propensity Score Matching Analysis - Zhou, Tian-han; Lin, Bei; Wu, Fan; Lu, Kai-ning; Mao, Lin-lin; Zhao, Ling-qian; Jiang, Ke-cheng; Zhang, Yu; Zheng, Wei-Jun; Luo, Ding-cun (Frontiers in Endocrinology, 2021)
ABSTRACT Purpose. To investigate the prognostic significance of extranodal extension (ENE) in papillary thyroid cancer (PTC). Methods. Seven hundred forty-three PTC patients were enrolled in the study from January 2014 to December 2017. The patients were dichotomized according to the presence of ENE. Logistic analysis was used to compare differences between the two groups. Kaplan-Meier (K-M) curve and propensity score matching (PSM) analyses were used for recurrence-free survival (RFS) comparisons. Cox regression was performed to analyse the effects of ENE on RFS in PTC. Result. Thirty-four patients (4.63%) had ENE. Univariate analysis showed that age, tumour size, extrathyroidal extension, and nodal stage were associated with ENE. Further logistic regression analysis showed that age, extrathyroidal extension and nodal stage remained statistically significant. Evaluation of K-M curves showed a statistically significant difference between the two groups before and after PSM. Cox regression showed that tumour size and ENE were independent risk factors for RFS. Conclusions. Age>/=55 years, extrathyroidal extension, and lateral cervical lymph node metastasis were identified as independent risk factors for ENE. ENE is an independent prognostic factor in PTC.